Modifying an accident process and its justice system – From single narratives and retribution to multiple stories and restoration. (July 2021) - Heraghty, Derek; Dekker, Sidney W.A.; Rae, Andrew
Abstract: When an accident occurs, the treatment of workers afterwards can have a significant impact on learning within the organisation. This in turn is a key influence on the organisation's capacity to deal with future risk. The style of the accident analysis process chosen can have a considerable influence on the outcomes of the analysis and the treatment of those involved. In this paper, we report on a study into the design, introduction, and eventual sun-setting of a restorative justice process. The study found that restorative justice mechanisms can improve honesty, engagement and learning. However, the study also found that factors external to the formal accident response process have a considerable influence over the perception and execution of restorative justice. Successful management of these factors is important for realising the benefits of restorative justice for workplace accidents.